Genetic diversity and haplotype distribution of Pachymeniopsis gargiuli sp. nov. and P. lanceolata (Halymeniales, Rhodophyta) in Korea, with notes on their non‐native distributions. Issue 5 (20th August 2014) - Kim, Su Yeon; Manghisi, Antonio; Morabito, Marina; Yang, Eun Chan; Yoon, Hwan Su; Miller, Kathy Ann; Boo, Sung Min; De Clerck, O.
<x xml:space="preserve">Abstract</x> The red alga Pachymeniopsis lanceolata, formerly known as Grateloupia lanceolata, is a component of the native algal flora of northeast Asia and has been introduced to European and North American waters. It has been confused with a cryptic species collected from Korea and Italy. Our analyses of rbcL, cox3 and ITS from P. lanceolata and this cryptic species has revealed two distinct entities, forming a clade, which were clearly separated from its congeners and positioned with other Asian species. Here, we describe the cryptic species as P. gargiuli sp. nov., a species that differs from others by molecular sequence and subtle anatomical characters. We hypothesize that P. gargiuli may have been recently dispersed by anthropogenic vectors, possibly at or near the same time as was P. lanceolata. Our cox3 data set revealed that one haplotype of P. gargiuli, shared between Korea and Italy, and two haplotypes of P. lanceolata, commonly occurring in Korea and USA, are invasive haplotypes. This is the first report of the utility of the mitochondrial coding cox3 sequences in red algae.